2022
DOI: 10.1007/s11469-021-00738-1
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Media Exposure and Psychological Outcomes During the Initial Outbreak of COVID-19 in China

Abstract: During the initial outbreak of COVID-19 in China, people spent a lot of time viewing or listening to COVID-19-related media content. And according to the conservation of resources theory, COVID-19-related media exposure would be related to multiple psychological outcomes, and different contents would have different associations with different psychological outcomes. Therefore, the present study aimed to clarify these relationships and find out the most important psychological outcome correlated with COVID-19-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Harman single-factor test is the most popular approach to evaluating common method deviation. 153,154 The analysis extracted four principal components, with the first factor explaining 41.136% of the variance, lower than the 50% threshold typically used to suggest the presence of a common method bias, 155 which suggests no major issues with common method bias in this research.…”
Section: Common Methods Deviation Testmentioning
confidence: 87%
“…Harman single-factor test is the most popular approach to evaluating common method deviation. 153,154 The analysis extracted four principal components, with the first factor explaining 41.136% of the variance, lower than the 50% threshold typically used to suggest the presence of a common method bias, 155 which suggests no major issues with common method bias in this research.…”
Section: Common Methods Deviation Testmentioning
confidence: 87%
“…Some have shown that using SM, such as Facebook, Instagram, WhatsApp, and YouTube, has helped individuals find information and gain support (e.g., Saud et al, 2020), while others have associated SM use with loneliness and depression (e.g., Boursier et al, 2020;Lisitsa et al, 2020). While the previous study demonstrated the association between different content exposure through the internet to psychological outcomes (Zhang et al, 2022), the present study seeks to distinguish between two types of SM use: intensive and problematic. Therefore, we aim to identify the specific implication of each pattern of SM use for individuals' social and mental aspects (i.e., social support, loneliness, and life satisfaction) during the closure.…”
Section: Introductionmentioning
confidence: 86%
“…Network analysis is particularly useful for visualizing complex relationships between many variables. 21,22 Previously, researchers mostly focused on describing the characteristics of nodes and edges in a single network generated from a single population. For example, a prior study investigated 196 adults with bulimia nervosa (BN).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, many kinds of psychological outcomes were associated with disaster-related media engagement. Network analysis is particularly useful for visualizing complex relationships between many variables [ 21 , 22 ]. Previously, researchers mostly focused on describing the characteristics of nodes and edges in a single network generated from a single population.…”
Section: Introductionmentioning
confidence: 99%